Comparison between bougies and stylets for simulated tracheal intubation with the C-MAC D-blade videolaryngoscope. Issue 6 (June 2015) - Batuwitage, Bisanth; McDonald, Andrew; Nishikawa, Koji; Lythgoe, Daniel; Mercer, Simon; Charters, Peter
Abstract : BACKGROUND: The C-MAC D-blade is a new, highly angulated, videolaryngoscope blade designed for use in patients with difficult airways. Directing a tracheal tube into the trachea with any indirect viewing laryngoscope can be difficult, even with a good view of the laryngeal inlet. OBJECTIVE: To determine which introducing strategy is most suitable for use with the C-MAC D-blade videolaryngoscope. DESIGN: Observational manikin study. SETTING: Centre for Simulation and Patient Safety. PARTICIPANTS: Twenty-four anaesthetists of at least 12 months' of experience. INTERVENTIONS: Six tracheal tube introducer strategies (no tracheal tube introducer (TX); hockey stick stylet (SH); Gliderite stylet (SG); bougie with tube loaded distally, near its curved tip (BD); bougie with tube loaded proximally (BP); bougie unloaded until tracheal placement (BU)) for each of two laryngoscopy settings (easy and difficult) in a SimMan 3G manikin. Two intubation attempts, with a maximum time allowance of 60 s each, were allowed for all laryngoscopy setting/introducer combinations. MAIN OUTCOME MEASURES: Time to intubate in seconds. Secondary outcome was overall subjective difficulty using a visual analogue scale. RESULTS: In the easy laryngoscopy setting, time to intubation was [median (interquartile range): SH 8.5 sec (7 to 11); SG 10 (8 to 11.5); BD 11 (10 to 12.5); TX 11 (7 to 31.5); BP 12 (11 to 13.5); BU 13 (11 to 14.5). There was no evidence of an overall difference in introducer strategies for time to intubate ( P  < 0.025) with SG and SH found to be favourable when compared with BU, and SH was also favourable when compared with BP. In the difficult laryngoscopy setting, time to intubation was: SG 11.5 (10 to 17.5); SH 14 (12 to 22); BD 15.5 (12 to 23.5); BU 16.5 (14 to 21); BP 16.5 (15.5 to 20.5); TX 60 (26.5 to 60). There was evidence of an overall difference in introducer strategies for time to intubate ( P  < 0.025) with all introducers found to be favourable compared with TX. SG was found to be favourable when compared with BU and BP. In groups TX and SH, anaesthetists failed to intubate in 13 of 24 cases and 1 of 24 cases, respectively. The visual analogue scores tended to reflect intubation times, more so in the difficult setting. CONCLUSION: The differences in time to intubate in both the easy and difficult laryngoscopy settings were minor for the different introducer strategies studied. The stylet introducers tended to take less time, but this did not result in important statistical differences. When using the C-MAC D-blade videolaryngoscope for simulated tracheal intubation, stylets and bougies performed in a similar fashion.